Coating composition for endoscope, lubricating member for endoscope, method for producing lubricating member for endoscope, flexible tube for endoscope, and endoscope
By using an endoscope coating composition containing a solid lubricant, a thermosetting resin, a solvent and a nonionic dispersant, the problem of the coating layer deterioration after wear during bending operation and sterilization of the endoscope components is solved, and excellent bending durability and sterilization resistance are achieved.
Patent Information
- Application Number
- CN202380055413.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-07
AI Technical Summary
The endoscope components wear due to friction during bending operation, and the coating layer deteriorates after sterilization by low temperature gas, affecting sliding durability.
The endoscope coating composition containing a solid lubricant, a thermosetting resin, a solvent and a nonionic dispersant is used, and a coating layer is formed on the surface of the endoscope component by spraying or the like, thereby improving bending durability and sterilization resistance.
The bending durability and sterilization resistance of the endoscope components are significantly improved, and the service life of the coating layer is extended.
Smart Images

Figure BDA0005252044440000031 
Figure BDA0005252044440000141 
Figure BDA0005252044440000211
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition for an endoscope, a lubricating member for an endoscope, a method for producing the lubricating member for an endoscope, an endoscope flexible tube, and an endoscope. Background Art
[0002] An endoscope is a medical device for observing the inside of a patient's body (the digestive tract, trachea, body cavity, etc.). Some endoscopes are equipped with treatment instruments and are configured to be able to perform various treatments while being inserted into the body.
[0003] The endoscope includes a bending portion that can be bent toward the front end side of the insertion portion so as to change the direction of the observation field of view to any direction. As for the bending portion, for example, a wire composed of twisted wires formed by bundling bare metal wires such as stainless steel is inserted into the insertion portion of the endoscope, and the wire is stretched by controlling an operating portion at hand, thereby bending the bending portion in a desired direction. The wire is inserted into a wire guide provided on the inner wall of the insertion portion of the endoscope, and is fixed in a manner that allows it to slide along the inner wall of the insertion portion of the endoscope. The operation of the bending portion using the wire itself is a function possessed by a general endoscope, and is disclosed in, for example, Patent Document 1. As a general structure of the wire and the wire guide in the bending portion, for example, reference can be made to Patent Document 1. Figure 2 wait.
[0004] Due to the bending operation of the bending portion, friction will occur between the above-mentioned wire and the wire guide, and the accompanying wire wear becomes a problem. In order to reduce this wear, the wire surface is usually coated with a solid lubricant composed of inorganic particles or organic particles (for example, Patent Document 2).
[0005] The coating treatment using solid lubricants is generally carried out by preparing a coating composition (coating agent) in which the solid lubricant is dispersed in a medium, and applying the coating composition to the surface of the coated part by spraying or the like. A solvent is used as a medium in the coating composition, and a resin is usually formulated as a binder. For such a coating composition in which the solid lubricant is dispersed in a medium, a technique of formulating a dispersant or a surfactant in order to improve the dispersion stability of the solid lubricant particles has been studied.
[0006] For example, among compositions containing a solid lubricant, a thermosetting resin as a binder, and a solvent, Patent Document 3 describes a composition in which a nitrogen-containing compound is formulated as a dispersant, and Patent Document 4 describes a composition in which a fluorinated surfactant is formulated as a dispersant.
[0007] Previous technical literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2018 / 034021
[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-208962
[0011] Patent Document 3: Japanese Patent Application Publication No. 2010-116336
[0012] Patent Document 4: International Publication No. 2020 / 250676 Summary of the invention
[0013] Technical issues to be solved by the invention
[0014] When the coated part formed with the coating layer containing a solid lubricant is an endoscope part represented by the above-mentioned wire, it is required to be able to slide smoothly for a long time (sliding durability). The results of the inventor's research show that the ability to fully maintain the coating state of the wire with the coating layer (bending durability) relative to the repeated bending operation of the wire has a great influence on the sliding durability.
[0015] It was also found that many endoscope parts having a coating layer containing a solid lubricant are sterilized by low-temperature gas sterilization (H2O2 gas sterilization) having strong chemical reactivity, and there is a problem that the coating layer deteriorates due to the sterilization.
[0016] The present invention aims to provide a coating composition for endoscopes which has excellent dispersion stability of a solid lubricant and can impart excellent bending durability and sterilization resistance to the endoscope components by forming a coating layer by applying the coating composition to the surface of the endoscope components. In addition, the present invention aims to provide a lubricating component for endoscopes which has been coated with the coating composition and a method for manufacturing the same. Furthermore, the present invention aims to provide an endoscope flexible tube and an endoscope using the lubricating component for endoscopes.
[0017] Means for solving technical problems
[0018] That is, the above-mentioned problems of the present invention are solved by the following means.
[0019] [1]
[0020] A coating composition for endoscope, wherein:
[0021] The invention contains a solid lubricant, a thermosetting resin, a solvent, and a nonionic dispersant. The nonionic dispersant is a compound composed of at least one element selected from the group consisting of carbon, hydrogen, oxygen, and nitrogen.
[0022] [2]
[0023] The coating composition for endoscope according to [1], wherein
[0024] The above-mentioned dispersant contains a compound having an alkyleneoxy group.
[0025] 〔3〕
[0026] The coating composition for endoscope according to [2], wherein
[0027] The compound having an alkyleneoxy group has an aromatic ring group.
[0028] [4]
[0029] The coating composition for endoscope according to [2] or [3], wherein
[0030] The above-mentioned alkyleneoxy group includes a propyleneoxy group.
[0031] 〔5〕
[0032] The coating composition for endoscope according to any one of [1] to [4], wherein
[0033] The molecular weight of the above dispersant is 100-2000.
[0034] [6]
[0035] The coating composition for endoscope according to any one of [1] to [5], wherein
[0036] The thermosetting resin includes a polyamide-imide resin.
[0037] 〔7〕
[0038] The coating composition for endoscope according to [6], wherein
[0039] The polyamide-imide resin contains a structural unit represented by the following formula (1) as a constituent component of polyamide-imide.
[0040] [Chemical formula 1]
[0041]
[0042] In the formula, Ar represents a divalent group having an aromatic ring.
[0043] 〔8〕
[0044] The coating composition for endoscope according to [7], wherein
[0045] Ar in the above formula (1) represents a phenylene group, a diphenylene methane group, a diphenylene propane group, a diphenylene ether group or a diphenylene amino group.
[0046] 〔9〕
[0047] The coating composition for endoscope according to any one of [6] to [8], wherein
[0048] The weight average molecular weight of the polyamide-imide resin is 10,000 to 100,000.
[0049] 〔10〕
[0050] The coating composition for endoscope according to any one of [1] to [9], wherein
[0051] The solid lubricant comprises inorganic particles, and the inorganic particles comprise at least one of graphite, graphite fluoride, graphene, carbon nanotubes and boron nitride.
[0052]
[11]
[0053] The coating composition for endoscope according to
[10] , wherein
[0054] The particle size of the inorganic particles is 0.5 to 70 μm.
[0055]
[12]
[0056] The coating composition for endoscope according to
[11] , wherein
[0057] The particle size of the inorganic particles is 1.0 to 50 μm.
[0058] 〔13〕
[0059] The coating composition for endoscope according to any one of [1] to
[12] , wherein
[0060] The solid lubricant includes organic particles, and the organic particles include at least one of fluororesin, melamine cyanurate and benzoguanamine.
[0061]
[14]
[0062] The coating composition for endoscope according to
[13] , wherein
[0063] The particle size of the organic particles is 0.5 to 30 μm.
[0064] 〔15〕
[0065] The coating composition for endoscope according to
[14] , wherein
[0066] The particle size of the organic particles is 1.0 to 10 μm.
[0067]
[16]
[0068] The coating composition for endoscope according to any one of [1] to
[15] , wherein
[0069] The solvent includes at least one of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, γ-butyrolactone and 1,3-dimethyl-2-imidazolidinone.
[0070]
[17]
[0071] A lubricating component for an endoscope, wherein:
[0072] The endoscope is coated with the coating composition according to any one of [1] to
[16] .
[0073]
[18]
[0074] The lubricating component for an endoscope according to
[17] , wherein:
[0075] The lubricating component for an endoscope is a lubricating wire for an endoscope.
[0076]
[19]
[0077] A method for manufacturing a lubricating component for an endoscope, wherein:
[0078] The production method comprises applying the endoscope coating composition described in any one of [1] to
[16] onto the surface of an endoscope component.
[0079] 〔20〕
[0080] A flexible tube for an endoscope, wherein:
[0081] It includes the lubricating component for endoscope described in
[17] or
[18] .
[0082] 〔twenty one〕
[0083] An endoscope, wherein
[0084] It comprises the flexible tube for endoscope described in
[20] .
[0085] In the present invention, a structure that does not explicitly describe whether it is substituted or unsubstituted means that the structure may have any substituent as long as the desired effect is achieved.
[0086] In the present invention, a numerical range represented by "to" means that the numerical values described before and after the range are included as the lower limit and the upper limit.
[0087] Effects of the Invention
[0088] The coating composition for endoscope of the present invention is excellent in the dispersion stability of the solid lubricant, and can impart excellent bending durability and sterilization resistance to the endoscope component by being applied to the surface of the endoscope component to form a coating layer.
[0089] In addition, the lubricating component for endoscope of the present invention is excellent in bending durability and sterilization resistance. In addition, according to the manufacturing method of the lubricating component for endoscope of the present invention, the lubricating component for endoscope with excellent bending durability and sterilization resistance can be obtained. In addition, the flexible tube for endoscope and the endoscope of the present invention are assembled with the lubricating component for endoscope of the present invention, and the lubricating component is excellent in bending durability and sterilization resistance. That is, the flexible tube for endoscope and the endoscope of the present invention are excellent in bending durability and sterilization resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 This is an external view showing the structure of one embodiment of an electronic endoscope.
[0091] Figure 2 It is an explanatory diagram of the sliding property test in the example. DETAILED DESCRIPTION
[0092] [Coating composition for endoscope]
[0093] The coating composition for endoscope of the present invention (hereinafter also referred to as the composition of the present invention) contains a solid lubricant, a thermosetting resin, a solvent, and a nonionic dispersant (N) described below.
[0094] <Solid lubricant>
[0095] The solid lubricant contained in the composition of the present invention can be widely used as a substance generally used as a solid lubricant. Therefore, the solid lubricant used in the present invention may be inorganic particles or organic particles, or a combination of these. The "solid" in the solid lubricant means that it is solid at 25°C.
[0096] Examples of materials for the solid lubricant composed of inorganic particles (also referred to as "inorganic solid lubricant" in the present invention) include graphite, graphite fluoride, graphene, carbon nanotubes, and boron nitride, and one or more of them are preferably used.
[0097] When the solid lubricant is an inorganic particle, the particle size can be set to, for example, 0.5 to 70 μm. From the viewpoint of further improving the bending durability, the particle size is preferably 1.0 to 50 μm. From the viewpoint of further improving the dispersion stability of the liquid, the bending durability and the resistance to hydrogen peroxide gas sterilization, the particle size is more preferably 3.5 to 40 μm, further preferably 4.0 to 30 μm, and further preferably 4.0 to 25 μm.
[0098] In the present invention or specification, the particle size of the solid lubricant refers to the maximum diameter (the distance from one point to another point on the outer circumference of the observed particle is the largest) of 100 particles randomly observed under an electron microscope when viewed from above, and the particle size of the solid lubricant refers to the arithmetic mean of the 100 maximum diameters.
[0099] As materials of the solid lubricant composed of organic particles (also referred to as "organic solid lubricant" in the present invention), for example, fluororesins, melamine cyanurate and benzoguanamine can be cited, and at least one of them is preferably contained. As fluororesins, polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF) can be cited, among which PTFE is preferred.
[0100] When the solid lubricant is an organic particle, the particle diameter can be 0.5 to 30 μm, or 1.0 to 10 μm, and preferably 2.0 to 9 μm.
[0101] The composition of the present invention preferably contains at least inorganic particles as a solid lubricant, and more preferably contains inorganic particles and organic particles.
[0102] When the composition of the present invention contains inorganic particles and organic particles as solid lubricants, the mass ratio of the content of the two particles is preferably [inorganic particles] / [organic particles] ≥ 0.3, and more preferably [inorganic particles] / [organic particles] ≥ 0.5. The upper limit is preferably [inorganic particles] / [organic particles] ≤ 3.0, and more preferably [inorganic particles] / [organic particles] ≤ 2.0. That is, preferably 0.3 ≤ [inorganic particles] / [organic particles] ≤ 3.0, and more preferably 0.5 ≤ [inorganic particles] / [organic particles] ≤ 2.0.
[0103] In the composition of the present invention, the content of the solid lubricant is preferably 10 to 50% by mass, more preferably 10 to 40% by mass, and even more preferably 10 to 30% by mass.
[0104] <Nonionic dispersant (N)>
[0105] The nonionic dispersant contained in the composition of the present invention is a compound composed of at least one element selected from the group consisting of carbon, hydrogen, oxygen and nitrogen. In this specification, the nonionic dispersant is also referred to as "nonionic dispersant (N)".
[0106] In the present invention, "nonionic dispersant" means a dispersant having substantially neither an acid value nor an amine value, and is a dispersant having a nonionic hydrophilic group. Therefore, the acid value of the nonionic dispersant (N) is 15 mgKOH / g or less, and the amine value is 15 mgKOH / g or less.
[0107] The acid value is a value measured by indicator titration, potentiometric titration or indicator photometric titration in accordance with JIS (Japanese Industrial Standards) K 2501 (2003). When the compound does not have a carboxyl group or a salt thereof, the acid value is 0 mgKOH / g.
[0108] The amine value is a value measured by indicator titration or potentiometric titration according to JIS K 2501 (2003). When the compound does not have any of amino groups (unsubstituted, primary, secondary) and ammonium groups (unsubstituted, primary to tertiary), the amine value is 0 mgKOH / g.
[0109] In the present invention, a compound "composed of at least one element of carbon, hydrogen, oxygen and nitrogen" means that the compound has at least one element of carbon, hydrogen, oxygen and nitrogen, and does not contain elements other than carbon, hydrogen, oxygen and nitrogen as constituent elements.
[0110] For example, the nonionic dispersant (N) does not contain fluorine. As shown in Comparative Example 2 described later, when a nonionic dispersant containing fluorine is used, its extremely high hydrophobicity (low surface energy) reduces the adhesion between the coating layer formed by the coating composition for endoscope and the coated part (substrate), and thus the bending durability is poor.
[0111] On the other hand, it means that the nonionic dispersant (N) may contain a small amount of elements other than carbon, hydrogen, oxygen and nitrogen (except fluorine) within a range that does not impair the effect of the present invention. Examples of elements that may be contained in the nonionic dispersant (N) include sulfur, silicon, phosphorus, boron and chlorine.
[0112] The total ratio (at%) of the number of carbon atoms, oxygen atoms and nitrogen atoms to the total number of all atoms excluding hydrogen atoms constituting the nonionic dispersant (N) is preferably 97 at% or more, more preferably 99.0 at% or more, further preferably 99.5 at% or more, and particularly preferably 100 at%.
[0113] The nonionic dispersant (N) preferably does not contain nitrogen as a constituent element, that is, is preferably a compound composed of carbon, hydrogen, and oxygen.
[0114] The nonionic dispersant (N) acts on the solid lubricant to improve the dispersibility of the solid lubricant in the solvent (medium). It is presumed that the nonionic dispersant (N) interacts with the medium in an affinity manner in the nonionic water-soluble group and is adsorbed to the solid lubricant in the remainder, thereby acting as a dispersant for the solid lubricant.
[0115] The linking portion between the nonionic water-soluble group and the remainder responsible for adsorption to the solid lubricant is not particularly limited within the range not impairing the effects of the present invention, and examples thereof include ether bonds, ester bonds, amide bonds, and urethane bonds, among which ether bonds or ester bonds are preferred, and ether bonds are more preferred.
[0116] As the nonionic dispersant (N), for example, polyoxyalkylene dispersants, amide dispersants, polyester polymer dispersants, acrylic polymer dispersants, polyurethane polymer dispersants, alkyl polyglycosides, sucrose fatty acid esters, sorbitan fatty acid esters, polyvinyl alcohol (PVA), methyl cellulose, ethyl cellulose, gelatin, etc. can be used.
[0117] Examples of the nonionic water-soluble group include alkyleneoxy groups (preferably polyalkyleneoxy groups) such as polyoxyethylene groups, polyoxypropylene groups, and polyoxybutylene groups, polyglyceryl groups, and sorbitan groups. The nonionic dispersant (N) preferably has one or more of these groups.
[0118] Among them, the nonionic dispersant (N) preferably contains a compound having an alkyleneoxy group.
[0119] In the present invention, the “alkyleneoxy group” includes a monoalkyleneoxy group having one alkyleneoxy structure and a polyalkyleneoxy group having a polyalkyleneoxy structure in which two or more alkyleneoxy structures are repeated.
[0120] In the polyalkyleneoxy group, the average repeating number of the alkyleneoxy structure is preferably 2 to 50, more preferably 2 to 20. In the present invention, the average in the average repeating number means a numerical average, for example, a value measured and calculated by GPC (gel permeation chromatography) or NMR (nuclear magnetic resonance analysis).
[0121] In the alkyleneoxy group, the number of carbon atoms of the alkylene group constituting the alkyleneoxy structure is preferably an integer of 2 to 10, more preferably an integer of 2 to 6, and further preferably 2 or 3. Examples of the alkyleneoxy structure in the alkyleneoxy group include an ethyleneoxy structure, a propyleneoxy structure, and a butyleneoxy structure. In the polyalkyleneoxy group, two or more alkyleneoxy structures may be present.
[0122] From the viewpoint of affinity for solvents, two adjacent oxygen atoms constituting the polyalkyleneoxy structure are preferably linked by an ethylene group (-CC-) or a 1,3-propanediyl group (-CCC-). In addition, the C in -CC- or -CCC- may be substituted by an alkyl group (carbon atom).
[0123] As the alkyleneoxy structure in the alkyleneoxy group, a propyleneoxy structure is preferred from the viewpoint of further improving the resistance to hydrogen peroxide gas sterilization, that is, the alkylene in the above-mentioned alkyleneoxy group is preferably a propylene group. Here, the propylene group constituting the propyleneoxy group may also be any one of 1,3-propanediyl and 1,2-propanediyl, preferably including 1,2-propanediyl. In addition, the nonionic dispersant (N) having an alkyleneoxy group may also have an alkyleneoxy structure other than a propyleneoxy structure (for example, an ethyleneoxy structure).
[0124] From the viewpoint of affinity with the solvent, the alkyleneoxy group is preferably a group having a polyoxyalkylene structure, and more preferably a group having a polypropyleneoxy structure. In addition, when the alkyleneoxy group is a group having a polypropyleneoxy structure, it may also have a polyalkyleneoxy structure (e.g., a polyethyleneoxy structure) other than the polypropyleneoxy structure.
[0125] The compound having an alkyleneoxy group preferably has an aromatic ring group.
[0126] The aromatic ring group may be any of an aryl group and a heteroaryl group.
[0127] The aryl group may be a monocyclic group or a condensed ring group, and is preferably a monocyclic group. The number of carbon atoms in the aryl group (including the number of carbon atoms in the substituents that the aryl group may have) is preferably 6 to 50, more preferably 6 to 46, and further preferably 6 to 38.
[0128] The aryl group may be unsubstituted or may have a substituent. Examples of the substituent that the aryl group may have include an alkyl group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms), an alkenyl group (preferably having 2 to 6 carbon atoms, more preferably 2 to 4 carbon atoms), an aryl group (preferably having 6 to 10 carbon atoms, more preferably 6 carbon atoms), an alkoxy group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms) and an aryloxy group (preferably having 6 to 10 carbon atoms, more preferably 6 carbon atoms), and the like. These groups may be substituted by an alkyl group and an aryl group. Specific examples of the substituent that the aryl group may have include a styryl group, a benzyl group, a cumyl group, a naphthyl group, a biphenyl group and a phenoxy group.
[0129] The heteroaryl group is an aromatic heterocyclic group composed of carbon atoms and heteroatoms (oxygen atoms, sulfur atoms, etc.), and may be a monocyclic group or a condensed ring group. The number of atoms constituting the aromatic heterocyclic ring is preferably 5 to 20, more preferably 5 to 14. The number of heteroatoms among the atoms constituting the ring is preferably 1 to 3, more preferably 1 to 2.
[0130] Examples of the heteroaryl group include furyl, thienyl, and benzofuranyl.
[0131] The heteroaryl group may be unsubstituted or may have a substituent, and as the substituent that the heteroaryl group may have, the description of the substituent that the above-mentioned aryl group may have can be applied.
[0132] The aromatic ring group is preferably an aryl group.
[0133] As the nonionic dispersant (N), a polyoxyalkylene dispersant is preferred. In addition, the polyoxyalkylene dispersant refers to a nonionic dispersant having the above-mentioned alkyleneoxy group (monoalkyleneoxy group or polyalkyleneoxy group).
[0134] Examples of the polyoxyalkylene dispersant include polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, polyoxyalkylene aryl ethers, polyoxyalkylene sorbitan fatty acid esters, and polyoxyalkylene fatty amides. It is preferred that at least one of these be contained, more preferred that at least one of polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, polyoxyalkylene aryl ethers, and polyoxyalkylene sorbitan fatty acid esters be contained, and further preferred that a polyoxyalkylene aryl ether be contained.
[0135] As the polyoxyalkylene group in these polyoxyalkylene dispersants, the description related to the above-mentioned alkyleneoxy group (monoalkyleneoxy group or polyalkyleneoxy group) can be applied, and examples thereof include ethyleneoxy group (monoethyleneoxy group or polyethyleneoxy group) and propyleneoxy group (monopropyleneoxy group or polypropyleneoxy group), and groups having these groups in common (monoethyleneoxy group, monopropyleneoxy group or polyethyleneoxy group, polypropyleneoxy group, etc.).
[0136] The polyoxyalkylene alkyl ether may be any of polyoxyalkylene monoalkyl ether and polyoxyalkylene dialkyl ether, preferably polyoxyalkylene monoalkyl ether. The alkyl group in the polyoxyalkylene alkyl ether preferably has 6 to 20 carbon atoms, more preferably 8 to 18 carbon atoms, and may be either linear or branched, preferably linear. In addition, the polyoxyalkylene alkyl ether may have a structure in which the alkyl portion is derived from a polyol such as glycerol, and polyoxyalkylene glycerol ether may be cited as an example of such a structure.
[0137] The polyoxyalkylene fatty acid ester may be any of polyoxyalkylene mono-fatty acid ester and polyoxyalkylene di-fatty acid ester, preferably polyoxyalkylene mono-fatty acid ester. The fatty acid group in the polyoxyalkylene fatty acid ester preferably has 6 to 20 carbon atoms, more preferably 8 to 18 carbon atoms, and may be either linear or branched, preferably linear.
[0138] As the polyoxyalkylene sorbitan fatty acid ester, at least one of the four hydroxyl groups of sorbitan is bonded to a polyoxyalkylene group, and at least one of the four hydroxyl groups of sorbitan and / or the polyoxyalkylene group forms at least one fatty acid ester with a fatty acid. As the fatty acid group in the polyoxyalkylene sorbitan fatty acid ester, the description of the fatty acid group in the above-mentioned polyoxyalkylene fatty acid ester can be preferably applied.
[0139] The polyoxyalkylene fatty amide may be any of polyoxyalkylene mono-fatty amide and polyoxyalkylene di-fatty amide. As the fatty acid group in the polyoxyalkylene fatty amide, the description of the fatty acid group in the polyoxyalkylene fatty acid ester can be preferably applied.
[0140] The polyoxyalkylene aryl ether may be any of polyoxyalkylene monoaryl ether and polyoxyalkylene diaryl ether, but polyoxyalkylene monoaryl ether is preferred.
[0141] As the aryl group in the polyoxyalkylene aryl ether, the above-mentioned description of the aryl group can be preferably applied, and examples thereof include phenyl and naphthyl groups which may be substituted with nonyl, phenyl, styryl, benzyl, cumyl, naphthyl, biphenyl or phenoxy groups. When the phenyl and naphthyl groups have nonyl, phenyl, styryl, benzyl, cumyl, naphthyl, biphenyl or phenoxy groups as substituents, the number thereof is not particularly limited, and can be, for example, 1 to 5.
[0142] Examples of the polyoxyalkylene aryl ethers include styrylphenol compounds (polyoxyalkylene styrylphenyl ethers) such as polyoxyethylene styrylphenyl ether, polyoxyethylene distyrylphenyl ether, polyoxyethylene tristyrylphenyl ether, and polyoxyethylene tetrastyrylphenyl ether; benzylphenol compounds such as polyoxyethylene benzylphenyl ether, polyoxyethylene dibenzylphenyl ether, and polyoxyethylene tribenzylphenyl ether; cumylphenol compounds such as polyoxyethylene cumylphenyl ether; nonylphenol compounds (polyoxyalkylene nonylphenyl ether) such as polyoxyethylene nonylphenyl ether; polyoxyethylene naphthylphenyl ether, polyoxyethylene naphthyl ether, polyoxyethylene biphenyl ether, and polyoxyethylene phenoxyphenyl ether. Among these examples, compounds in which a polyoxyethylene moiety is substituted with polyoxypropylene (e.g., polyoxypropylene monostyrylphenyl ether) and compounds in which a polyoxyethylene moiety is substituted with polyoxyethylene polyoxypropylene (e.g., polyoxyethylene polyoxypropylene monostyrylphenyl ether) are also preferably used.
[0143] The average repeating number of the polyoxyalkylene group in the polyoxyalkylene aryl phenyl ether such as the polyoxyethylene group in the polyoxyethylene aryl phenyl ether is preferably 1 to 30, more preferably 2 to 30, and further preferably 15 to 30. When the repeating number is 1 or more, there is a tendency that the miscibility with aqueous solvents etc. is excellent. In addition, when the repeating number is 30 or less, there is a tendency that the viscosity is not too high.
[0144] Among the polyoxyalkylene aryl phenyl ethers, it is also preferred to contain at least one of polyoxyalkylene styryl phenyl ethers such as polyoxyethylene styryl phenyl ether, polyoxypropylene styryl phenyl ether and polyoxyethylene polyoxypropylene styryl phenyl ether, and polyoxyalkylene nonyl phenyl ethers such as polyoxyethylene nonyl phenyl ether, polyoxypropylene nonyl phenyl ether and polyoxyethylene polyoxypropylene nonyl phenyl ether. In addition, the number of styryl groups or nonyl groups of the phenyl group substituted with the phenyl ether is not particularly limited, and may be 1 to 5.
[0145] The number average molecular weight (Mn) of the nonionic dispersant (N) is preferably 100 or more, more preferably 200 or more, and further preferably 300 or more. The upper limit is preferably 4000 or less, more preferably 2000 or less, further preferably 1500 or less, and particularly preferably 1000 or less. That is, the number average molecular weight (Mn) of the nonionic dispersant (N) is preferably 100 to 4000, more preferably 100 to 2000, further preferably 200 to 1500, and particularly preferably 300 to 1000.
[0146] In the present invention, the number average molecular weight is a value measured by the method described in Examples described below, and is also simply referred to as molecular weight in the present invention.
[0147] The HLB (Hydrophile-Lipophile Balance) value of the nonionic dispersant (N) is usually 2 to 18, preferably 4 to 16, more preferably 6 to 15, and particularly preferably 9 to 14.
[0148] In the present invention, the HLB value of the nonionic surfactant is a value measured by an emulsification method according to the method described in "Handbook - Cosmetics / Preparation Raw Materials - Revised Edition", Nikko Chemical Co., Ltd., revised edition published on February 1, 1974, pages 854-855.
[0149] The nonionic dispersant (N) can improve the adhesion between the coating layer and the member to be coated (substrate) in the member to be coated whose surface is coated with the composition of the present invention, and as a result, it is estimated that excellent bending durability can be exhibited.
[0150] The adhesion of the left and right substrate and the coating layer is mainly adhesive, and it is of vital importance to improve the bonding strength of adhesive (thermosetting resins such as polyamide-imide resins) and SUS (substrate). The present inventor has found that in the case of a coating composition using a dispersant of a solid lubricant in the past, the charge associated with the ionic bond of the adhesive and the substrate is neutralized by the ionic group possessed by the dispersant, reducing the adhesion of the adhesive and the substrate. Therefore, it is believed that by using a nonionic dispersant rather than a dispersant with an acid value and / or an amine value, the reduction of the adhesion of the adhesive and the substrate can be suppressed, and excellent bending durability can be shown.
[0151] In particular, the use of a dispersant having an aromatic ring group as the nonionic dispersant (N) tends to improve adhesion with a solid lubricant, particularly graphite composed of carbon, and is preferred from the viewpoint of obtaining more excellent bending durability.
[0152] Furthermore, the nonionic dispersant (N) can suppress the degradation of the coating layer caused by sterilization treatment in the member to be coated whose surface is coated with the composition of the present invention, and as a result, it is estimated that the member can exhibit excellent sterilization resistance.
[0153] When subjected to low-temperature gas sterilization treatment with strong chemical force, the chemical bonds of the organic components are mainly cut, the adhesive components are degraded, and thus the coating layer is degraded. The inventors of the present invention know that the degradation of the coating layer caused by H2O2 gas is particularly prone to occur in components with small molecular weight. Although the amount added is small, the degradation of the adhesive component occurs due to the degradation of the dispersant. The nonionic dispersant (N) used in the present invention is a nonionic dispersant without acid value and / or amine value. It is a compound composed of limited specific elements such as carbon, hydrogen, and at least one of oxygen and nitrogen. Therefore, it is presumed that it is not easy to be degraded by H2O2 gas, and the overall sterilization resistance of the coating layer is improved.
[0154] In particular, when the nonionic dispersant (N) is a compound having the above-mentioned alkyleneoxy group (monoalkyleneoxy group or polyalkyleneoxy group), in particular, when a dispersant having a propyleneoxy structure is used as the alkyleneoxy structure constituting the alkyleneoxy group, the H2O2 gas resistance is further improved. It is presumed that the presence of the -CH3 group in the side chain suppresses the severance of the molecular chain constituting the main chain with respect to the active radicals derived from the potent H2O2 gas.
[0155] Similarly, when exposed to H2O2 gas, an acidic atmosphere is formed, so a dispersant having an ether structure in which ester bonds and amide bonds are easily cut and which is resistant to pH changes is preferred. Moreover, a compound having an aromatic ring group is preferred because it is superior in sterilization resistance compared to an aliphatic compound lacking in oxidation stability.
[0156] When the nonionic dispersant (N) has a polymer structure, the polymer structure is not particularly limited, and for example, a random polymer type, a block polymer type, or a graft polymer type copolymer is preferred.
[0157] For example, when the nonionic dispersant (N) is a polymer, a good nonionic dispersant (N) can be obtained by conventional methods by copolymerizing a monomer component having the above-mentioned nonionic water-soluble group with another monomer component having lower hydrophilicity (or higher hydrophobicity) than the monomer component.
[0158] In addition, the nonionic dispersant (N) can also be obtained from a commercial source. Examples of the nonionic dispersant (N) that can be obtained from a commercial source include the following products.
[0159] Commercially available products of polyoxyethylene styryl phenyl ether are all referred to by their trade names, for example, Takesurf D-6112, Takesurf D-6115, Takesurf D-6120, Takesurf D-6131, Takesurf D-6512, Takesurf D-6413, DTD-51 and Takesurf D-6320 (all manufactured by Takemoto Oil & Fats Co., Ltd.); TS-1500, TS-2000, TS-2600 and SM-174N (all manufactured by Toho Chemical Co., Ltd.); EMULGEN A-60, EMULGEN A-90 and EMULGEN A-500 (all manufactured by Kao Corporation).
[0160] As polyoxyethylene naphthyl ether, commercial products are all sold under the trade names, and examples thereof include NOIGEN EN series (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) and Takesurf D-7240 (manufactured by Takemoto Yuzu Kyo Co., Ltd.).
[0161] In the composition of the present invention, the content of the nonionic dispersant (N) is preferably 0.1 to 20 mass %, more preferably 0.1 to 15 mass %, further preferably 0.2 to 10 mass %, further preferably 0.2 to 8 mass %, further preferably 0.2 to 5 mass %, further preferably 0.2 to 3 mass %, particularly preferably 0.3 to 2 mass %.
[0162] <Thermosetting resin>
[0163] The composition of the present invention contains a thermosetting resin. In the member to be coated treated with the composition of the present invention, the thermosetting resin acts as a binder, and can highly improve the bending durability and sterilization resistance of the member to be coated.
[0164] The thermosetting resin is not particularly limited. For example, polyamide-imide resin, polyimide resin (including substances present as polyamic acid in the composition), epoxy resin, phenol resin, melamine resin and urea resin can be cited. Among them, the thermosetting resin preferably includes polyamide-imide resin, and the thermosetting resin is more preferably polyamide-imide resin.
[0165] The polyamide-imide resin preferably contains a structural unit represented by the following formula (1) as a constituent component of polyamide-imide.
[0166] [Chemical formula 2]
[0167]
[0168] In the formula, Ar represents a divalent group having an aromatic ring.
[0169] Ar is preferably phenylene, diphenylmethane (-phenylene-CH2-phenylene-), diphenylpropane (-phenylene-C3H6-phenylene-), diphenyleneether (-phenylene-O-phenylene-), diphenylenesulfonate (-phenylene-SO2-phenylene-), diphenylamine (-phenylene-NH-phenylene-), biphenyldiyl (-phenylene-phenylene-), or naphthalenediyl, and more preferably phenylene, diphenylmethane, diphenylpropane, diphenylether or diphenylamine.
[0170] The content of the structural unit represented by the above formula (1) in the above polyamideimide is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. The above polyamideimide is also preferably in the form of a structure composed of the structural unit represented by the above formula (1).
[0171] The weight average molecular weight of the polyamide-imide resin is preferably 10,000 to 100,000, more preferably 20,000 to 80,000, and further preferably 25,000 to 60,000.
[0172] In the present invention, the weight average molecular weight is a value measured by the method described in Examples described later.
[0173] In the composition of the present invention, the content of the thermosetting resin is preferably 0.5 to 20% by mass, more preferably 1 to 15% by mass, further preferably 2 to 10% by mass, and particularly preferably 3 to 8% by mass.
[0174] In the composition of the present invention, the content of the nonionic dispersant (N) is preferably 0.5 to 50 parts by mass, more preferably 1 to 30 parts by mass, further preferably 1 to 20 parts by mass, and particularly preferably 2 to 15 parts by mass, based on 100 parts by mass of the solid lubricant.
[0175] In the composition of the present invention, the content of the thermosetting resin is preferably 1 to 50 parts by mass, more preferably 5 to 70 parts by mass, further preferably 10 to 60 parts by mass, and particularly preferably 12 to 50 parts by mass, based on 100 parts by mass of the solid lubricant.
[0176] In addition, in the composition of the present invention, the content of the nonionic dispersant (N) is preferably 2 to 100 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 80 parts by mass, further preferably 5 to 70 parts by mass, further preferably 5 to 60 parts by mass, further preferably 6 to 50 parts by mass, and particularly preferably 6 to 40 parts by mass, relative to 100 parts by mass of the thermosetting resin.
[0177] <Solvent>
[0178] The composition of the present invention contains a solvent as a dispersion medium for the solid lubricant. The solvent is not particularly limited as long as it functions as a dispersion medium. As the solvent, an organic solvent is preferably used.
[0179] Examples of the solvent that can be used in the composition of the present invention include aprotic polar solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, γ-butyrolactone and 1,3-dimethyl-2-imidazolidinone, and xylene.
[0180] The composition of the present invention preferably contains, as a solvent, one of the solvents that can be used in the composition of the present invention, including at least one of the aprotic polar solvents described above, or a combination of two or more thereof.
[0181] In the composition of the present invention, the ratio of the total amount of aprotic polar solvents to the total amount of solvents can be, for example, 40% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more. In addition, it is also preferred that all solvents are aprotic polar solvents.
[0182] In the composition of the present invention, the content of the above-mentioned solvent can function as a dispersion medium for the solid lubricant, and is not particularly limited as long as it can form a composition together with the thermosetting resin. For example, the content of the solvent in the composition of the present invention can be set to 10 to 90% by mass, preferably 20 to 85% by mass, more preferably 20 to 80% by mass, and further preferably 40 to 80% by mass.
[0183] In addition to the above-mentioned components, the composition of the present invention can appropriately contain various commonly used additives within the range that does not impair the effects of the present invention. Such additives include, for example, plasticizers, colorants, defoamers, surfactants, dispersants, and the like.
[0184] <Preparation of coating composition for endoscope>
[0185] The composition of the present invention can be obtained by uniformly mixing the above-mentioned components using a homogenizer or the like.
[0186] In the present invention, the term "composition" means not only a form in which each component is uniformly present in the composition but also a form in which a part of the components is non-uniformly present within a range that does not impair the effects of the present invention.
[0187] The composition of the present invention can be suitably used as a coating agent for imparting sliding properties (lubricity) to various components (endoscope components) used in an endoscope. For example, it can be applied to the surface of a wire inserted into the endoscope insertion portion in order to bend the curved portion of the endoscope insertion portion in a desired direction. Therefore, the friction between the wire and the wire guide can be effectively reduced, and the bending durability and sterilization resistance of the wire can be improved. In addition, it can also be applied to the surface of the resin coating layer of the flexible tube for an endoscope.
[0188] [Lubricating parts for endoscopes]
[0189] The lubricating component for endoscope of the present invention (hereinafter also referred to as "lubricating component of the present invention") is a component for endoscope which has been coated with the composition of the present invention. The method of coating treatment using the composition of the present invention is not particularly limited. For example, the composition of the present invention is applied to the surface of the coated component, and then the solvent is removed by drying, thereby coating the surface of the coated component with a solid lubricant (forming a coating layer on the surface of the coated component). The above-mentioned coating can be carried out by a spraying method, a dipping method, a coating method using a brush or a roller, or a rod coating method. In addition, after the composition of the present invention is applied to the surface of the above-mentioned coated component, it is heated to cure the thermosetting resin. Therefore, in the lubricating component of the present invention, the thermosetting resin in the composition of the present invention exists in a thermosetting state. Regarding the timing of the above-mentioned heating, it can be any one of the simultaneous removal of the solvent by the above-mentioned drying and / or after the removal of the solvent. In addition, the conditions such as the heating temperature and the heating time during the above-mentioned heating can be appropriately adjusted according to the type of the thermosetting resin as long as the thermosetting resin can be cured.
[0190] The thickness of the coating layer is not particularly limited as long as the effects of the present invention are achieved, and can be, for example, 1 to 500 μm, preferably 5 to 100 μm. In the present invention, the thickness of the coating layer is a value measured by the method described in the Examples described below.
[0191] The lubricating member of the present invention is preferably a lubricating wire for endoscope. As described above, the lubricating wire for endoscope can be obtained by applying the composition of the present invention to the surface of the wire to be inserted into the insertion portion of the endoscope.
[0192] [Flexible tube for endoscope and endoscope]
[0193] The endoscope of the present invention includes the endoscope flexible tube of the present invention.
[0194] The preferred form of the endoscope of the present invention is described by taking an electronic endoscope as an example. The electronic endoscope is used as a medical device that is assembled with an endoscope flexible tube (hereinafter, the endoscope flexible tube is sometimes referred to as a "flexible tube") and the flexible tube is inserted into a body cavity to observe the body cavity. Figure 1 In the example shown, the electronic endoscope 2 includes an insertion portion 3 inserted into a body cavity, a main body operation portion 5 connected to the base end portion of the insertion portion 3, and a universal cord 6 connected to a processor device or a light source device. The insertion portion 3 is composed of a flexible tube 3a connected to the main body operation portion 5, a curved portion 3b (corner portion 3b) connected to the flexible tube 3a, and a front end portion 3c connected to the front end of the curved portion 3b and having a built-in imaging device (not shown) for intracavitary photography. The flexible tube 3a, which occupies most of the length of the insertion portion 3, is flexible over almost the entire length, and in particular, the portion inserted into the body cavity or the like is more flexible. As described above, the curved portion 3b is configured to be able to be bent in a desired direction by stretching a wire that is inserted into the insertion portion 3 and fixed to the inner wall of the curved portion 3b by a wire guide. As an example of a method of bending using a wire, for example, reference can be made to the disclosure of Japanese Patent Application Laid-Open No. 2009-180. Figure 1 wait.
[0195] The flexible tube for endoscope of the present invention includes the lubricating member of the present invention. As described above, examples of the lubricating member included in the flexible tube for endoscope of the present invention include a wire material, a resin coating layer, and the like.
[0196] [Example]
[0197] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0198] [Example 1]
[0199] <Preparation Example 1-1> Preparation of coating composition for endoscope (C-1)
[0200] Into a container of a small homogenizer (manufactured by Nippon Seiki Seisaku-sho, trade name: EXCEL AUTO HOMOGENIZER ED-7, blade diameter 45 mmφ) were placed 20.0 g (5.2 g in terms of solid content, 14.8 g of N-methyl-2-pyrrolidone) of a polyamide-imide resin solution (manufactured by Risenoko Co., Ltd. (formerly Showa Denko Materials Co., Ltd.), trade name: HPC-6000-26, thermosetting resin, weight average molecular weight 40,000, solid content concentration: 26% by mass) , 37.2 g of N-methyl-2-pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., first-class reagent), 22.3 g of p-xylene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., first-class reagent), and a nonionic dispersant (polyoxyethylene octyl ether, manufactured by Takemoto Oil & Fats Co., Ltd., trade name: Takesurf D-1004, HLB value 11.5) 0.5 g was added and mixed by stirring at 1000 rpm (rotations per minute) for 5 minutes.
[0201] Next, 20.0 g of graphite powder (manufactured by Fuji Graphite Industries, Ltd., trade name: MF-10N, particle size: 10 μm) was added and mixed by stirring at 3000 rpm for 30 minutes to obtain a coating composition of Example 1.
[0202] <Preparation Example 1-2> Preparation of lubricating member for endoscope -1
[0203] The coating composition of Example 1 was sprayed on the entire surface of a stainless steel wire (SUS303, φ0.5 mm) using a hand spray gun. Then, the polyamide-imide resin was cured by heating and drying in an oven at 230°C for 20 minutes to prepare a lubricating wire for endoscope of Example 1. In the lubricating wire for endoscope, the film thickness of the coating layer was 19 μm. With respect to the film thickness, the film thickness was randomly measured at five locations using a micrometer, and the average value of the measured values at the five points was adopted.
[0204] [Examples 2 to 41] and [Comparative Examples 1 to 3]
[0205] Each coating composition of Examples 2 to 41 and Comparative Examples 1 to 3 was obtained in the same manner as in Preparation Example 1-1 except that the raw materials used were changed as shown in the following table.
[0206] Next, using these coating compositions, lubricating wire materials for endoscopes of Examples 2 to 41 and Comparative Examples 1 to 3 were obtained in the same manner as in Preparation Example 1-2.
[0207] In each of the lubricating wire materials for endoscopes of Examples 2 to 41 and Comparative Examples 1 to 3, the film thickness of the coating layer measured in the same manner as in Example 1 was 10 to 30 μm.
[0208] The obtained coating composition and lubricating wire for endoscope were evaluated as follows. The results are summarized in the following table.
[0209] [Test Example 1] Evaluation of liquid dispersion stability
[0210] The viscosity (I) of the coating composition prepared in each of the above preparation examples immediately after preparation was measured by the following measurement method. Next, each coating composition was left to stand at 5° C. for 30 days. Thereafter, the coating composition was stirred at 100 rpm for 30 minutes, and the viscosity (II) was measured again by the following measurement method.
[0211] <Viscosity measurement method>
[0212] The value of dynamic complex viscosity at 27° C. and 10 Hz was measured using RheoStress RS6000 (trade name) manufactured by HAAKE, and the value was used as the viscosity of the coating composition. The unit of viscosity is Pa·s.
[0213] The viscosity change rate (%) was calculated from the following formula using the obtained viscosities (I) and (II), and the viscosity change rate was compared with the following evaluation criteria to evaluate the dispersion stability.
[0214] Viscosity change rate (%) = 100 × [viscosity (II) - viscosity (I)] / viscosity (I)
[0215] <Evaluation criteria for liquid dispersion stability>
[0216] A: The viscosity change rate is less than 10%, and no solids accumulate on the bottom of the container
[0217] B: The viscosity change rate is 10% or more and less than 100%, and no solids accumulate on the bottom of the container
[0218] C: The viscosity change rate is more than 100%, and no solids accumulate on the bottom of the container
[0219] D: The viscosity change rate is more than 100%, and solids accumulate on the bottom of the container
[0220] “Solids accumulate on the bottom of the container” means that when the coating composition is taken out of the container after standing at 5° C. for 30 days, a viscous liquid or solid with a viscosity of 1000 Pa·s or more remains on the bottom of the container.
[0221] [Test Example 2] Evaluation of bending durability
[0222] The lubricating wire for endoscope produced in each of the above preparation examples was wound around a pulley with a diameter of 20 mm for one turn, and a bending test was performed by sliding back and forth 100 times in the longitudinal direction while applying a tension of 10 gf (1 kgf = 9.8 N) to observe the peeling of the coating layer. In the case where the coating layer did not peel off, the pulley diameter was reduced, and the bending test was performed in the same manner as when the pulley with a diameter of 20 mm was used, and the bending test was performed by reducing the pulley diameter until peeling occurred. The pulley diameter used when peeling occurred was compared with the following standard to evaluate the bending durability.
[0223] <Bending durability evaluation criteria>
[0224] AA: less than 8mm
[0225] A: 8mm or more and less than 12mm
[0226] B: 12mm or more and less than 16mm
[0227] C: 16mm or more and less than 20mm
[0228] D: 20mm
[0229] [Test Example 3] Evaluation of Sterilization Resistance with Hydrogen Peroxide Gas
[0230] The lubricating wire for endoscope produced in the above method is used Figure 2 The test equipment shown is used to carry out the sliding characteristics test. Figure 2 As shown, the lubricating wire material (12) for endoscope obtained in each of the above preparation examples is set on a φ5 mm SUS rod (14) and pulleys (13, 15) at an angle (α) of 100 degrees. A load of 10 N is applied by a counterweight (16) to set this state as the initial state of the test.
[0231] Next, the stroke (A) was set to 10 mm, the weight was pulled downward at a speed of 100 mm / min, and then returned to the original state. This operation was set as one reciprocation, and the maximum stress measured by the dynamometer (11) during this one reciprocation was recorded.
[0232] Next, the wire material for which the maximum stress has been measured is subjected to 100 repetitions of low-temperature plasma sterilization treatment according to the advanced program of a hydrogen peroxide gas sterilizer ("STERRAD (registered trademark) NX" manufactured by ASP). Afterwards, the maximum stress is measured by the same sliding characteristic test as above. The maximum stress before the above sterilization treatment is set as "PSB(2)", and the maximum stress after the above sterilization treatment is set as "PSA(2)". The ratio of "PSA(2)" to "PSB(2)" {(PSA(2) / PSB(2))×100(%)} is calculated, and the hydrogen peroxide gas sterilization resistance is evaluated by comparing with the following standards.
[0233] Furthermore, the maximum stress PSB(2) before sterilization of each lubricating wire for endoscope of Examples 1 to 41 was less than 20 N, showing lubricity at a level that poses no problem in practical use.
[0234] <Evaluation Criteria>
[0235] AA: above 80%
[0236] A: 60% or more and less than 80%
[0237] B: 40% or more and less than 60%
[0238] C: 20% or more and less than 40%
[0239] D: Less than 20%
[0240] [Determination of molecular weight]
[0241] In addition, the number average molecular weight (Mn) of the dispersant and the binder and the weight average molecular weight (Mw) of the binder are measured as molecular weights converted to polystyrene by GPC (gel permeation chromatography). At this time, a GPC device HLC-8220 (trade name, manufactured by Tosoh Corporation) is used, THF (tetrahydrofuran) is used as the eluent, and a chromatographic column is used G3000HXL+G2000HXL (trade name), and an RI detector (Refractive Index Detector) is used under the measurement conditions of 23°C and a flow rate of 1 mL / min.
[0242] [Table 1]
[0243]
[0244] [Table 2]
[0245]
[0246] [Table 3]
[0247]
[0248] [Table 4]
[0249]
[0250] [Table 5]
[0251]
[0252] In the above-mentioned table, the allocation amount of each raw material refers to the mass parts accounting for 100 mass parts of coating composition. In addition, except the allocation amount of solvent, each allocation amount of adhesive, solid lubricant and dispersant is the allocation amount (solid content) except the solvent contained by raw material. In addition, about the solvent contained by raw material, the allocation amount as solvent is recorded in the table.
[0253] Blank columns and “-” in the table mean that the raw material is not contained.
[0254] Hereinafter, each raw material described in the above table will be described.
[0255] [Binder (B)]
[0256] (B-1): Polyamide-imide resin (manufactured by Risenoco Co., Ltd. (formerly Showa Denko Materials Co., Ltd.), trade name: "HPC-6000-26", weight average molecular weight 40,000, structural unit Ar of formula (1) is a thermosetting resin of diphenylmethane structure, solid content concentration 26 mass %)
[0257] (B-2): Polyimide resin (manufactured by Unitika Co., Ltd., trade name: "U-imide AR", trade name: polyamic acid, which becomes polyimide resin by thermal curing reaction, solid content concentration: 18% by mass)
[0258] (B-3): Amorphous polyester resin (manufactured by Toyobo Co., Ltd., trade name: "VYLON 200", number average molecular weight: 17,000, solid content: 100% by mass)
[0259] [Dispersant (D)]
[0260] (D-1): Polyoxyethylene octyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-1004", HLB value 11.5, number average molecular weight 480)
[0261] (D-2): Polyoxyethylene lauryl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-1105", HLB value 10.8, number average molecular weight 510)
[0262] (D-3): Polyoxyethylene lauryl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-1103-D", HLB value 8.1, number average molecular weight 530)
[0263] (D-4): Polyoxyethylene stearyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-1402", HLB value 4.9, number average molecular weight 590)
[0264] (D-5): Polyoxypropylene dodecyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-1106DIR", HLB value 11.6, number average molecular weight 730)
[0265] (D-6): polyethylene glycol monostearate (manufactured by Nihon Emulsion Co., Ltd., trade name: "EMALEX 810", HLB value 11, number average molecular weight 620)
[0266] (D-7): polyethylene glycol distearate (manufactured by Nihon Emulsion Co., Ltd., trade name: "EMALEX 600di-S", HLB value 8, number average molecular weight 840)
[0267] (D-8): Polyoxyethylene polystyrylphenyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-6112", HLB value 10.9, number average molecular weight 630)
[0268] (D-9): Polyoxypropylene polystyrylphenyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-6105-W", HLB value 11.1, number average molecular weight 890)
[0269] (D-10): polyoxyethylene cumyl phenyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-7010", HLB value 13.3, number average molecular weight 460)
[0270] (D-11): Polyoxyethylene polyoxypropylene nonylphenyl ether (manufactured by Aoki Oil & Fats Industry Co., Ltd., trade name: "Blaunon NPP-0802R", HLB value 13.5, number average molecular weight 640)
[0271] (D-12): Polyoxyethylene naphthyl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-7213-W", HLB value 12.2, number average molecular weight 470)
[0272] (D-13): Polyoxyethylene sorbitan oleate (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf D-945", HLB value 15.0, number average molecular weight 620)
[0273] (D-14): Polyoxyethylene glyceryl ether monostearate (manufactured by Nihon Emulsion Co., Ltd., trade name: "EMALEX GM-10", HLB value 11, number average molecular weight 1,700)
[0274] (D-15): Polyoxyalkylene diglyceryl ether (manufactured by Takemoto Oil & Fats Co., Ltd., trade name: "Takesurf K-17", HLB value 11.2, number average molecular weight 2,700)
[0275] (D-16): Polyoxyethylene perfluoroalkyl ether (manufactured by DIC Corporation, trade name: "MEGAFACE F-444", HLB value 8.5, number average molecular weight 630)
[0276] In addition, (D-1) to (D-16) all had an acid value of 0 mgKOH / g and an amine value of 0 mgKOH / g.
[0277] [Inorganic solid lubricant (S)]
[0278] (S-1): Graphite (manufactured by Fuji Graphite Industries, trade name: "MF-10N", particle size: 10 μm)
[0279] (S-2): Graphite (manufactured by Fuji Graphite Industries, trade name: "RCG-1Q", particle size: 1.0 μm)
[0280] (S-3): Graphite (manufactured by Fuji Graphite Industries, trade name: "RCG-3Q", particle size: 3.2 μm)
[0281] (S-4): Graphite (manufactured by Fuji Graphite Industries, trade name: "MF-20N", particle size 20 μm)
[0282] (S-5): Graphite (manufactured by Fuji Graphite Industries, trade name: "ACG-45J", particle size 45 μm)
[0283] (S-6): Graphite (manufactured by Fuji Graphite Industries, trade name: "SC-120", particle size: 63 μm)
[0284] (S-7): Fluorinated graphite particles (manufactured by Chuo Glass Co., Ltd., trade name: "CEFBON CMC", particle size 5.0 μm, denoted as "F-graphite" in the table)
[0285] (S-8): Graphene particles (manufactured by EM Japan, trade name: "Graphene Nanopowder G-12S", particle size 4.5 μm, denoted as "graphene" in the table)
[0286] (S-9): Carbon nanotube (manufactured by Microphase, trade name: "TNCNT", particle size 5.0 μm, denoted as "CNT" in the table)
[0287] (S-10): Boron nitride particles (manufactured by Denka Co., Ltd., trade name: "SP-2", particle size 4.0 μm, denoted as "BN" in the table)
[0288] [Organic solid lubricant (G)]
[0289] (G-1): Polytetrafluoroethylene particles (produced by Kitamura Co., Ltd., trade name: "KTL-2N", particle size 3.0 μm, denoted as "PTFE" in the table)
[0290] (G-2): Melamine cyanurate particles (manufactured by Nissan Chemical Industries, Ltd., trade name: "MC-6000", particle size 2.0 μm, described as "melamine" in the table)
[0291] (G-3): Benzoguanamine particles (manufactured by Nippon Shokubai Co., Ltd., trade name: "Epostar L15", particle size 9 μm, denoted as "guanamine" in the table)
[0292] -Solvents-
[0293] NMP: N-methyl-2-pyrrolidone
[0294] PX: p-xylene
[0295] The following can be learned from the results in the above table.
[0296] As shown in Comparative Example 1, when the coating composition containing a solid lubricant, a thermosetting resin and a solvent does not originally contain a dispersant, and the coating layer on the surface of the wire formed by the coating composition does not contain a dispersant, the dispersion stability, bending durability and hydrogen peroxide gas sterilization resistance of the liquid are all poor. As shown in Comparative Example 2, when a fluorinated surfactant is used as a dispersant, the dispersion stability of the liquid is improved relative to Comparative Example 1, but the bending durability is poor, and the hydrogen peroxide gas sterilization resistance is slightly improved. In addition, as shown in Comparative Example 3, although it contains a nonionic dispersant (N) specified in the present invention, it contains a thermoplastic resin instead of a thermosetting resin. In the case, relative to Comparative Example 1, the dispersion stability of the liquid is improved, but the bending durability and hydrogen peroxide gas sterilization resistance are poor.
[0297] In contrast, as shown in Examples 1 to 41, the coating compositions of the present invention containing the nonionic dispersant (N) specified in the present invention are all excellent in the dispersion stability of the liquid, and the wires having a coating layer formed on the surface using these coating compositions are all excellent in the two characteristics of bending durability and hydrogen peroxide gas sterilization resistance. In particular, in Examples 8 to 12 in which the nonionic dispersant (N) has an alkyleneoxy group and an aromatic ring group, the dispersion stability of the liquid, the bending durability and the hydrogen peroxide gas sterilization resistance are more excellent. In addition, in Examples 5, 9 and 11 in which the nonionic dispersant (N) has a polypropyleneoxy group as an alkyleneoxy group, more excellent hydrogen peroxide gas sterilization resistance is shown. In addition, in the case where the thermosetting resin is a polyamideimide resin, it is more excellent in bending durability and hydrogen peroxide gas sterilization resistance (Example 28 relative to Example 31).
[0298] The present invention has been described together with its embodiments, but it is understood that unless otherwise specified, the present invention is not intended to be limited in any detail of the description, but should be broadly interpreted without violating the spirit and scope of the invention as shown in the appended claims.
[0299] This application claims priority based on Japanese Patent Application No. 2022-156219 filed in Japan on September 29, 2022, the contents of which are incorporated herein by reference as a part of the description of this specification.
[0300] DESCRIPTION OF SYMBOLS 2 Electronic endoscope (endoscope) 3 Insertion portion
[0301] 3a Flexible tube 3b Bend (corner)
[0302] 3c front end
[0303] 5Main operating unit
[0304] 6 Universal Cord
[0305] 11 Dynamometer
[0306] 12 Lubricating wire
[0307] 13, 15 pulley
[0308] 14SUS rod
[0309] 16 Counterweight
[0310] A stroke (10mm)
[0311] α angle (100 degrees)
Claims
1. A coating composition for endoscope, wherein: The invention contains a solid lubricant, a thermosetting resin, a solvent, and a nonionic dispersant. The nonionic dispersant is a compound composed of at least one element selected from the group consisting of carbon, hydrogen, oxygen, and nitrogen.
2. The coating composition for endoscope according to claim 1, wherein The dispersant includes a compound having an alkyleneoxy group.
3. The coating composition for endoscope according to claim 2, wherein The compound having an alkyleneoxy group has an aromatic ring group.
4. The coating composition for endoscope according to claim 2, wherein The alkyleneoxy group includes a propyleneoxy group.
5. The coating composition for endoscope according to claim 1, wherein The molecular weight of the dispersant is 100-2000.
6. The coating composition for endoscope according to claim 1, wherein The thermosetting resin includes a polyamide-imide resin.
7. The coating composition for endoscope according to claim 6, wherein The polyamide-imide resin contains a structural unit represented by the following formula (1) as a constituent component of polyamide-imide, [Chemical formula 1] In the formula, Ar represents a divalent group having an aromatic ring.
8. The coating composition for endoscope according to claim 7, wherein Ar in the formula (1) represents a phenylene group, a diphenylene methane group, a diphenylene propane group, a diphenylene ether group or a diphenylene amino group.
9. The coating composition for endoscope according to claim 6, wherein The weight average molecular weight of the polyamideimide is 10,000 to 100,000.
10. The coating composition for endoscope according to claim 1, wherein The solid lubricant comprises inorganic particles, and the inorganic particles comprise at least one of graphite, graphite fluoride, graphene, carbon nanotubes and boron nitride.
11. The coating composition for endoscope according to claim 10, wherein The particle size of the inorganic particles is 0.5 to 70 μm.
12. The coating composition for endoscope according to claim 11, wherein The particle size of the inorganic particles is 1.0 to 50 μm.
13. The coating composition for endoscope according to claim 1, wherein The solid lubricant includes organic particles, and the organic particles include at least one of fluororesin, melamine cyanurate and benzoguanamine.
14. The coating composition for endoscope according to claim 13, wherein The particle size of the organic particles is 0.5 to 30 μm.
15. The coating composition for endoscope according to claim 14, wherein The particle size of the organic particles is 1.0 to 10 μm.
16. The coating composition for endoscope according to claim 1, wherein The solvent includes at least one of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, γ-butyrolactone and 1,3-dimethyl-2-imidazolidinone.
17. A lubricating component for an endoscope, wherein: The endoscope is coated with the coating composition according to any one of claims 1 to 16.
18. The lubricating member for an endoscope according to claim 17, wherein: The lubricating component for an endoscope is a lubricating wire for an endoscope.
19. A method for manufacturing a lubricating component for an endoscope, wherein: The production method comprises applying the endoscope coating composition according to any one of claims 1 to 16 onto the surface of an endoscope component.
20. A flexible tube for an endoscope, wherein: The lubricating member for an endoscope according to claim 17 is included.
21. An endoscope, wherein: The endoscope comprises the endoscope flexible tube according to claim 20.
Citation Information
Patent Citations
Endoscope
JP2004208962A
Bending device of endoscope
JP2009000180A
Liquid porphyrin derivative
JP2010116336A
Endoscope
WO2018034021A1
Coating composition for endoscope, lubricating member for endoscope, production method for lubricating member for endoscope, flexible tube for endoscope, and endoscope
WO2020250676A1